THE ENHANCEMENT OF SKILL IN MENTION THE EXAMPLE AND IDENTIFYING CONCLUSION IN REACTION RATE MATERIAL BY GUIDED INQUIRY LEARNING MODEL - mila marlinda; ila rosilawati; tasviri efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This study aims to determine the effectiveness of guided inquiry learning model in improving the skills mentioned examples and identified conclusion in reaction rate material. Subjects in this study were students of class XI IPA2 SMAN 2 Gadingrejo totaling 34 people, consisting of 14 male students and 20 female students. This study used a pre-experimental method with One Group Pretest Posttest Design. Research cite skills mentioned examples and identified conclusion, data analysis used N-gain. The results showed n-Gain skills and identify examples mentioned conclusion is 0.63 (medium category) and persentation KKM 75%, identified conclusion is 0.66 (medium category) and persentatiaon KKM 85%. Based on the difference test,  this suggests learning guided inquiry model is effective in improving the skills mentioned examples and identify conclusions class XI IPA2 reaction rate on the material. Keywords: guided inquiry, the skills mentioned examples and skills identified conclusion, reaction rate